2015
DOI: 10.18632/oncotarget.6287
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 expression, activity andex vivosensitivity to the PARP inhibitor, talazoparib (BMN 673), in chronic lymphocytic leukaemia

Abstract: In chronic lymphocytic leukemia (CLL), mutation and loss of p53 and ATM abrogate DNA damage signalling and predict poorer response and shorter survival. We hypothesised that poly (ADP-ribose) polymerase (PARP) activity, which is crucial for repair of DNA breaks induced by oxidative stress or chemotherapy, may be an additional predictive biomarker and a target for therapy with PARP inhibitors.We measured PARP activity in 109 patient-derived CLL samples, which varied widely (192 – 190052 pmol PAR/106 cells) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…PARPi cause DNA damage accumulation and G2/M cell cycle arrest (23,24). Effects of ABT-263 and BMN 673 on DNA double-strand break induction and cell cycle progression were thus examined to dissect the potential mechanisms of cell growth inhibition induced by the combination treatment.…”
Section: Resultsmentioning
confidence: 99%
“…PARPi cause DNA damage accumulation and G2/M cell cycle arrest (23,24). Effects of ABT-263 and BMN 673 on DNA double-strand break induction and cell cycle progression were thus examined to dissect the potential mechanisms of cell growth inhibition induced by the combination treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, olaparib displayed activity in ATM-defective lymphoblastoid cell lines, the ATM -mutant mantle cell lymphoma cell line Granta-519, and ATM -defective primary CLL cells 54 , 55 . However, the ATM status-dependent specificity of PARP inhibitor sensitivity recently came into question, when it was shown that the PARP1/2 inhibitor talazoparib (BMN-673) displayed activity against CLL cells ex vivo independent of ATM and HR status 56 . Here we developed an autochthonous, non-transplant mouse model of ATM -deficient CLL to unequivocally demonstrate the in vivo activity and specificity of olaparib against ATM -defective CLL.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that a recent study, while confirming the cytotoxic activity of the potent PARP inhibitor talazoparib in patient-derived CLL cells, failed to find an association between PARP activity, ATM loss, or levels of oxidative DNA damage [53].…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 96%